Yeast culture improves growth, antioxidant status, immunity, and gut microbiota homeostasis in preweaning Holstein calves - Li, Xueqiang; Yang, Xiaolin; Liu, Shixiong; Liang, Xi; Chen, Hui; Liu, Dacheng (Frontiers in Veterinary Science, 2025)
IntroductionCalves in the lactation period exhibit limited disease resistance and stress tolerance, making them particularly vulnerable to health challenges such as diarrhoea. Yeast culture (YC) supplementation has emerged as a promising strategy to enhance health and growth in young ruminants. This study aimed to investigate the effects of YC supplementation on growth performance, antioxidant capacity, immune function, and intestinal microbiota composition in lactating Holstein calves.MethodsA total of 40 lactating Holstein calves were randomly assigned to either a control group or a YC-supplemented group, with the feeding trial lasting 60 days. Growth performance parameters were recorded, serum antioxidant and immune markers were evaluated, and gut microbial diversity and composition were analysed using metagenomic sequencing. Furthermore, correlations between microbial taxa and serum markers were assessed.ResultsThe results showed that YC supplementation significantly increased average daily gain (ADG) and feed intake, and reduced the incidence of diarrhoea (p < 0.05). Serum levels of total antioxidant capacity (T-AOC), total superoxide dismutase (T-SOD), and glutathione peroxidase (GSH-Px) were significantly elevated, while malondialdehyde (MDA) content was significantly decreased (p < 0.05), indicating improved antioxidant status. Immunoglobulin and cytokine levels were also significantly higher in the YC group (p < 0.05). Metagenomic analysis revealed a significant increase in the Chao index and a trend toward higher Shannon diversity in the YC group. YC supplementation notably increased the relative abundance of beneficial bacteria such as Phocaeicola plebeius, Ruminococcus sp., Segatella copri, and Candidatus Scatovivens faecipullorum, while reducing potentially pathogenic bacteria like Candidatus Cryptobacteroides sp. and Dorea sp. Correlation analysis showed that T-AOC was positively associated with P. plebeius and S. copri, while MDA was positively correlated with Candidatus Cryptobacteroides sp. and negatively correlated with Ruminococcus sp. and other beneficial taxa. Similarly, several immune markers exhibited positive correlations with beneficial bacteria and negative correlations with harmful bacteria. Functional pathway analysis suggests that YC may enhance immune responses and antioxidant capacity through activation of the T cell receptor and B cell receptor signalling pathways.DiscussionIn conclusion, YC supplementation improved growth performance, enhanced antioxidant and immune functions, and favourably modulated gut microbiota in lactating Holstein calves. These changes collectively contributed to reduced diarrhoea incidence and improved overall health, highlighting yeast culture as a valuable nutritional strategy for calf health management.